Looking at Ministry as Honor: A Correlation of Understanding Christian Ethics and Ministry in the Church - Nisa Amalia (EXOUSIA : Jurnal Pendidikan Agama Kristen, 2022)
Serving is a form of expression of our love for God and pleasing Him. The motivation to serve must be based on a correct understanding, viewing service as honor. This study aims to see the relationship between understanding Christian ethics and students' perspectives on ministry in the church. The research uses a quantitative approach, with instruments in the form of questionnaires. The object of the study were students, and the sample numbered thirty-five people. Based on the results of the data processing, a correlation coefficient of 0.602 was obtained which showed a positive relationship and was classified as a high correlation. Thus students need to be encouraged to understand Christian ethics correctly because it is also closely related to the way they view ministry in the church, so they will come to the understanding that service is honor.